Daniels' running formula - Daniels, Jack 1933-
"This book is for dedicated runners and running coaches. The first section of this edition presents general training information, considerations, and options that can contribute to the success of all runners, particularly how to determine optimal training intensity based on their own characteristics and goals. The second section then provides training advice and event- and distance-specific programs for those who participate in competitions"--Provided by publisher.